Subarachnoid hemorrhage in pituitary tumor - Ashis Patnaik; Ashok Kumar Mahapatra (Indian Journal of Neurosurgery)
Subarachnoid hemorrhage (SAH) is the bleeding into the subarachnoid space containing cerebrospinal fluid. The most common cause of SAH is trauma. Rupture of aneurysms, vascular anomalies, tumor bleeds and hypertension are other important etiologies. SAH in the setting of pituitary tumor can result from various causes. It can be due to intrinsic tumor related pathology, injury to surrounding the vessel during the operative procedure or due to an associated aneurysm. We discuss the pathological mechanisms and review relevant literature related to this interesting phenomenon. Early and accurate diagnosis of the cause of the SAH in pituitary tumors is important, as this influences the management.